Radio Free New Mexico (Cimarron, New Mexico Cimarron Legend, 1992)
Article on the new radio stations beginning and what it took to start the station.
Master List item # 110
File location is in the Raton File Cabinet
Keywords: O'Connell, Francis "Bo"; Lanson, Ken; Edlund, Bryan; 99.1 FM Radio; KAFR Radio Station; KILO-FM Radio; Alpine Air Tours; Radio station; Broadcasting; Public Speaking; New Business; Jazz; Bluegrass; Music; Cimarron, New Mexico; Angel Fire, New Mexico; Colorado Springs, New Mexico; Haley, Idaho